The distribution of covert microbial natural enemies of a globally invasive crop pest, fall armyworm, in Africa: Enemy release and spillover events. Issue 9 (22nd June 2022) - Withers, Amy J.; Rice, Annabel; de Boer, Jolanda; Donkersley, Philip; Pearson, Aislinn J.; Chipabika, Gilson; Karangwa, Patrick; Uzayisenga, Bellancile; Mensah, Benjamin A.; Mensah, Samuel Adjei; Nkunika, Phillip Obed Yobe; Kachigamba, Donald; et al.
Abstract: Invasive species pose a significant threat to biodiversity and agriculture world‐wide. Natural enemies play an important part in controlling pest populations, yet we understand very little about the presence and prevalence of natural enemies during the early invasion stages. Microbial natural enemies of fall armyworm Spodoptera frugiperda are known in its native region, however, they have not yet been identified in Africa where fall armyworm has been an invasive crop pest since 2016. Larval samples were screened from Malawi, Rwanda, Kenya, Zambia, Sudan and Ghana for the presence of four different microbial natural enemies; two nucleopolyhedroviruses, Spodoptera frugiperda NPV (SfMNPV) and Spodoptera exempta NPV (SpexNPV); the fungal pathogen Metarhizium rileyi ; and the bacterium Wolbachia . This study aimed to identify which microbial pathogens are present in invasive fall armyworm, and determine the geographical, meteorological and temporal variables that influence prevalence. Within 3 years of arrival, fall armyworm was exposed to all four microbial natural enemies. SfMNPV probably arrived with fall armyworm from the Americas, but this is the first putative evidence of host spillover from Spodoptera exempta (African armyworm) to fall armyworm for the endemic pathogen SpexNPV and for Wolbachia . It is also the first confirmed incidence of M. rileyi infecting fall armyworm in Africa. Natural enemies were localised, with variation being observed both nationally and temporally. The prevalence of SfMNPV (the most common natural enemy) was predominantly explained by variables associated with the weather; declining with increasing rainfall and increasing with temperature. However, virus prevalence also increased as the growing season progressed. The infection of an invasive species with a natural enemy from its native range and novel pathogens specific to its new range has important consequences for understanding the population ecology of invasive species and insect–pathogen interactions. Additionally, while it is widely known that temporal and geographic factors affect insect populations, this study reveals that these are important in understanding the distribution of microbial natural enemies associated with invasive pests during the early stages of invasion, and provide baseline data for future studies. Abstract : The infection of the invasive fall armyworm, with a natural enemy from its native range and novel pathogens from its new range, has important consequences for understanding the population ecology of invasive species and virus–insect interactions. The authors show that temporal and geographic factors are also important in understanding the distribution of microbial natural enemies.